Gross and Histomorphological Studies on the Respirat ory and Conducting Portions of Respiratory System in Goats (Capra hircus) - Khyalia, Vinit (Indian Journal of Veterinary Anatomy, 2020)
Six specimens of respiratory components viz. lungs with trachea of healthy local goat showed firm tubular structure of trachea. It was located directing caudally from cricoid cartilage of larynx to the hillus of lung and bifurcated into the right and left principal bronchus. The ciliated pseudostratified columnar epithelium with goblet cells lined the trachea. The serous coated pleura was there around the lung parietally and viscerally. The primary, secondary and tertiary bronchi were observed into the lung. The respiratory bronchioles, alveolar duct and alveoli has revealed the elastic and collagen fibres with predominance of the former.